Exploring controlled drug release from magneto liposomes - Podaru, George (Kansas State University, 2017)
This thesis focuses on exploring fast and controlled drug release from several liposomal drug delivery systems including its underlying mechanics. In addition, the construction of a pulsed high-voltage rotating electromagnet is demonstrated based on a nested Helmholtz coil design. Although lots of different drug delivery mechanisms can be used, fast drug delivery is very important to utilize drug molecules that are short-lived under physiological conditions. Techniques that can release model molecules under physiological conditions could play an important role to discover the pharmacokinetics of short-lived substances in the body. In this thesis, an experimental method is developed for the fast release of the liposomes’ payload without a significant increase in (local) temperatures. This goal is achieved by using short magnetic pulses to disrupt the lipid bilayer of liposomes loaded with magnetic nanoparticles. This thesis also demonstrates that pulsed magnetic fields can generate ultrasound from colloidal superparamagnetic nanoparticles. Generating ultrasound remotely by means of magnetic fields is an important technological development to circumvent some of the drawbacks of the traditional means of ultrasound generation techniques. In this thesis, it is demonstrated that ultrasound is generated from colloidal superparamagnetic nanoparticles when exposed to pulsed and alternating magnetic fields. Furthermore, a comparison between inhomogeneous and homogeneous magnetic fields indicates that both homogeneous and inhomogeneous magnetic fields could be important for efficient ultrasound generation; however, the latter is more important for dilute colloidal dispersion of magnetic nanoparticles. In strong magnetic fields, the ultrasound generated from the colloidal magnetic nanoparticles shows reasonable agreement with the magnetostriction effect commonly observed for bulk ferromagnetic materials. At low magnetic fields, the colloidal magnetic nanoparticle dispersion produces considerable amount of ultrasound when exposed to a.c. magnetic fields in the 20−5000 kHz frequency range. It is expected that the ultrasound generated from magnetic nanoparticles will have applications toward the acoustic induction of bioeffects in cells and manipulating the permeability of biological membranes
Keywords: Ultrasound generation; Magneto liposomes; Drug delivery